(untitled) (LEGAL DIALOGICA, 2025)
This study aims to find out and analyze the legal consequences for perpetrators of online fraud through electronic social media. To find out and analyze legal efforts for victims of online fraud on social media. This study uses an empirical legal research method by focusing on analyzing primary data and secondary data using qualitative data analysis techniques. The results of this study indicate that the legal consequences for perpetrators of online fraud through electronic social media. The application of legal sanctions for perpetrators of online investment fraud has not been expressly regulated in a special law that can provide criminal penalties for perpetrators but is regulated in the Criminal Code Article 372 with a maximum imprisonment of four years or a maximum fine of nine hundred rupiah, and Article 378 with a maximum imprisonment of 4 (four) years. Efforts to provide countermeasures in providing criminal policies are carried out with the criminalization aspect of criminal law, namely by forming special laws to regulate things that are prohibited in this case. Legal action is a solution provided by law to victims whose rights to justice are not fulfilled, as well as providing relief and peace of mind for the criminal acts that befell them. Online Fraud Actions involve the following steps such as Legal Efforts through Litigation, and Legal Efforts through Non-Litigation. This Research Recommendation Should be the Urgency of Making Regulations or Legal Arrangements for Investment or Commonly Called Online Capital Investment Specifically in Order to Provide Criminal Aggravation and Strengthen Criminal Sanctions for Online Fraud Perpetrators for the Purpose of the Law, namely Legal Certainty, Justice and Benefit. The State in Protecting Online Practices Should Make Regulations That Specifically and Firmly Regulate the Aspects of Investment Practices or Online Capital Investment in Order to Achieve Legal Certainty. Abstrak: Penelitian ini bertujuan Untuk Mengetahui dan Menganalisis akibat hukum bagi Pelaku tindak Pidana Penipuan Online melalui media sosial elektronikUntuk Mengetahui dan Menganalisis Upaya hukum bagi Korban Tindak Pidana Penipuan Online dia Media Sosial.Penelitian ini menggunakan metode penelitian hukum yuridis empiris dengan berfokus menganalisis data primer dan data sekunder menggunakan teknis analisis data kualitatif Hasil Penelitian Ini menunjukkan Bahwa Akibat Hukum Bagi Pelaku Tindak Pidana Penipuan Online Melalui Media Sosial Elektronik Penerapan sanksi hukum bagi pelaku penipuan investasi online belum secara tegas diatur dalam suatu undang-undang khusus yang bisa memberikan pemberatan pidana bagi pelaku namun diatur pada Kitab UndangUndang Hukum Pidana Pasal 372 dengan pidana penjara paling lama empat tahun atau pidana denda paling banyak sembilan ratus rupiah, dan Pasal 378 dengan pidana penjara paling lama 4 (empat) tahun.Upaya memberikan penangulangan dalam memberikan kebijakan pidana dilaksanakan dengan aspek kriminalisasi pada hukum pidana yakni dengan membentuk undang-undang khusus dalam mengatur hal hal yang dilarang dalam hal tersebut.Perbuatan hukum merupakan suatu penyelesaian yang diberikan undang-undang kepada korban yang tidak terpenuhi haknya atas keadilan, serta memberikan keringanan dan ketenangan jiwa atas tindak pidana yang menimpanya. Tindakan Penipuan Online melibatkan langkah-langkah berikut Seperti Uapaya Hukum Jalur Litigasi,Dan Upaya Hukum Halur Non Litigasi. Rekomendasi Penelitian Ini Seharusnya Urgensi pembuatan regulasi atau pengaturan hukum terhadap investasi atau biasa disebut penanaman modal online secara khusus agar bisa memberikan pemberatan pidana dan mempertegas sanksi pidana bagi pelaku penipuan online demi tujuan hukum yaitu kepastian hukum, keadilan dan kemanfaatan.Seharusnya negara dalam melindungi praktikonline membuat regulasi yang secara khusus dan tegas mengatur aspek-aspek yang ada pada praktik investasi atau penanaman modal online agar lebih tercapainya kepastian hukum.